A Reassessment of the Turkish Party System - Mustafa Bölükbaşı (Siyasal: Journal of Political Sciences)
Modern political institutions have a long history in Turkey but because of limited competition until 1945 and military interventions in 1960, 1971, 1980, and 1997, the party system has not developed consistently. Moreover, the electoral system, particularly the 10% electoral threshold applied after 1980, directly affected the Turkish party system. Having been interrupted by non-democratic forces and attempted to be formed via political engineering, the development of Turkish political parties and party systems has not been linear. In recent years, there has been an increasing amount of literature on the Turkish party system. However, since most studies were based on inadequate empirical data and limited to the 1990s and the 2000s, they have generally focused on the predominant party system and failed to critically review discussions on party systems. This paper analyzes Turkish party systems from 1950 to the present using the quantitative method. Adopting the criteria of the number of relevant parties and their relative strengths, this study applies different indicators such as the effective number of parties and fragmentation. This paper argues that Turkey has experienced four main different forms of party systems since 1950: a two-party system (1950-1960 and 2002), a two and a half party system (1960-1980), a moderate multiparty system with a balance among parties (1991-1999), and a moderate multiparty system with one dominant party (1983-1987, and 2007-2018).